ACTUALIZING A CITY AT THE DOWNSTREAM AREAS OF KALIMANTAN BY HANDIL SYSTEM (Jurusan Arsitektur UPR, 2018)
This study is aimed at formulating some alternatives to create a city in a downstream area of Kalimantan by adopting Handil system. The formulation study and analysis are based on the previous findings by which a Handil system found in a rural area before it transformed into an urban area. By such findings some alternatives are formulated to create a Handil city in a downstream area in Kalimantan.